Larval habitats impose trait-dependent limits on the direction and rate of adult evolution in dragonflies. (19th May 2021) - Moore, Michael P.
Abstract : Natural selection on juveniles is often invoked as a constraint on adult evolution, but it remains unclear when such restrictions will have their greatest impact. Selection on juveniles could, for example, mainly limit the evolution of adult traits that mostly develop prior to maturity. Alternatively, selection on juveniles might primarily constrain the evolution of adult traits that experience weak or context-dependent selection in the adult stage. Using a comparative study of dragonflies, I tested these hypotheses by examining how a species' larval habitat was related to the evolution of two adult traits that differ in development and exposure to selection: adult size and male ornamentation. Whereas adult size is fixed at metamorphosis and experiences consistent positive selection in the adult stage, ornaments develop throughout adulthood and provide context-dependent fitness benefits. My results show that species that develop in less stable larval habitats have smaller adult sizes and slower rates of adult size evolution. However, these risky larval habitats do not limit ornament expression or rates of ornament evolution. Selection on juveniles may therefore primarily affect the evolution of adult traits that mostly develop prior to maturity.